Post-war recovery in two exhibitions in Rome in Palazzo Venezia in the years 1944 and 1945 (ACME, 2024)
This paper aims to explain the historical-artistic context and the political significance of two exhibitions of the immediate postwar period held at Palazzo Venezia, Mussolini’s headquarters. They are the Exhibition of the masterpieces of European painting (XV-XVII centuries), which took place from August 1944 to February 1945, and the Italian Art Exhibition at Palazzo Venezia, inaugurated in May and finished in October 1945. The first one is organized and promoted by Allied Military Government, the second one by the National Association for the Restoration of War-Damaged Monuments, founded and directed by the philanthropist Umberto Zanotti Bianco. Numerous events are interlaced in the organization of these exhibitions: the work of the Monuments Men, the rescue work of the mobile artistic heritage by some former officials of the Ministry of National Education, the birth of the Allied Military Government and the new Italian anti-fascist institutions, the need to restore the destroyed artistic heritage and the foundation of Zanotti Bianco’s association. Therefore, anyone who wants to confront with the study of the historical-artistic situation of the Roman and national postwar period, must necessarily deal with the two exhibitions of Palazzo Venezia.
Keywords: Post-war exhibitions; Palazzo Venezia; Renaissance painting; protection of the artistic heritage; post-war reconstruction